Introduction to quantum mechanics - Griffiths, David J. (Noida: Pearson, 2015)
This text first teaches students how to apply the theories of quantum mechanics, and then provides them with a more insightful discussion of what it means. Fundamental principles are covered, quantum theory presented, and special techniques developed for solving realistic problems. The two-part coverage organizes topics under basic theory, and assembles an arsenal of approximation schemes with illustrative applications. The book avoids the temptation to include every possible relevant topic, in order to give students a complete treatment that is not oppressively long. It follows a straightforward writing style - entertains and informs without intimidating.
The wave function -- Time-independent Schrödinger equation -- Formalism -- Quantum mechanics in three dimensions -- Identical particles -- Time-independent perturbation theory -- The variational principle -- The WKB approximation -- Time-dependent perturbation theory -- The adiabatic approximation -- Scattering -- Measurement and interpretation -- Linear algebra
Includes index
Keywords: Quantum Mechanics